Effect of Alloying Elements on the Tooling Capabilities of High Speed Steels Fabricated by Powder Metallurgy - Toptop, Guven Orkun; Kisasoz, Alptekin; Karaaslan, Ahmet (CARL HANSER VERLAG, 2013)
SPM 10 and ASP 2052 alloys fabricated by powder metallurgy have a higher alloying elements content than rolled types. Such higher alloying contents improve the mechanical properties of tool steels and provide a longer tooling life. In this study, the effects of alloying elements and different heat treatments processes on the properties of SPM 10 and ASP 2052 were investigated. Also, the effects of alloying elements and process parameters on the mechanical properties as well as tooling abilities of the specimens were studied. The specimens were characterized by Rockwell hardness tests and the tooling abilities of the specimen were determined by characterizing the number of screws that could be fabricated with specimens. According to the results of the experiments, higher hardness values were obtained at elevated austenitization temperatures. Besides, the presence of Co as an alloying element evolved better hot work properties of the specimens.
Keywords: Materials Science